CRYSTAL STRUCTURE OF BONE MARROW TYROSINE KINASE FROM CHROMOSOME X WITH COVALENT LIGANDS - Sousa, Bárbara Beatriz da Costa Botelho (2021)
"Bone marrow tyrosine kinase in chromosome X (BMX) is a major member of the TEC family kinases and has been implicated in tumorigenecity, motility, proliferation and differentiation. BMX is highly overexpressed in prostate cancer and it is involved in the adaptive compensatory mechanism of castrate-resistance prostate cancer to androgen deprivation therapy. Besides, it suppresses a core component of the intrinsic apoptotic pathway, granting tumor cells the ability to escape apoptosis induced by chemotherapeutic drugs. BMX knockout mouse have a normal lifespan, without an obvious altered phenotype, suggesting that therapies based on BMX inhibition, may have limited side effects. We developed a series of BMX-IN-1 analogues that showed an increased inhibitory capacity when compared to BMX-IN-1. Since crystallographic information is essential to understand the molecular basis of BMX inhibition by covalent inhibitors we establish a baculovirus-insect expression system protocol for the production of the recombinant human BMX. Here we report the full biochemical and biophysical characterization of human BMX alone and in complex with different covalent ligands.(...)"